Key factors in intranet migration - Markkanen, Laura (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The purpose of this thesis is to identify the key factors to be considered in intranet migration, and to investigate how the migration process differs from the first time intranet implementation. The aim was to compare the key factors of both processes, and study whether using SharePoint as the tool for intranet management affects these factors. First, a framework for intranet implementation key factors was created based on earlier research, and the findings were used as guidance in studying an intranet migration project at Royal Philips. The study was conducted in the Procurement function, and the data for the research was collected from an intranet migration project within the function. The results show that while many of the key factors in intranet migration are similar to the key factors of first time intranet implementation, there are also differences. Similarities include the importance of considering management and control mechanisms, top management support, and content, while differences could be seen in training, communication, and roles required in the process. A new important factor found in the migration project concerns the process of analyzing the existing intranet and identifying possible problems areas, so that the new intranet can be planned in a way that avoids them.